EKSPERIMENTASI MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE AND SHARE) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PERBANDINGAN DI MTS AL-HIKMAH PATI TAHUN AJARAN 2021/2022 - Khofifah Munawaroh; Nanang Nabhar Fakhri Auliya (IKIP Siliwangi, 2022)
This study aims to find out which is better between the SSCS (Search, Solve, Create and Share) learning model and the direct learning model on students' critical thinking skills in comparative material at MTs Al-Hikmah Pati in the 2021/2022 academic year. This type of research uses a true experimental design in the form of Posttest-Only Group Design. The sampling technique in this study is cluster random sampling. The population in this study was the seventh grade female students of MTs Al-Hikmah. The data collection technique of this research is with tests and documentation. The results of this study are the first, namely students' critical thinking skills on comparative material using the SSCS learning model with an average result of 80.79 including in the high category. Second, the average posttest result data shows that there is a difference in students' critical thinking skills, which is 80.79 for the experimental class, and 64.40 for the control class. This is evidenced by the value of the results of the independent sample t-test, from the calculations obtained t count = 4.034 > t table = 2.003 so that H0 is rejected and H1 is accepted. This means that the SSCS (Search, Solve, Create, Share) learning model is better than the direct learning model on students' critical thinking skills in comparative material at MTs Al-Hikmah Pati for the 2021/2022 academic year.